The springsweet - Mitchell, Saundra (Boston : Harcourt, 2012)
Moving from Baltimore to Oklahoma Territory in the late 1800s, seventeen-year-old Zora experiences the joys and hardships of pioneer life, discovering new love and her otherworldly power.
Companion book to: The Vespertine.
Keywords: Supernatural -- Fiction; Love -- Fiction; Frontier and pioneer life -- Oklahoma -- Fiction